Sleep Disorders and Risk Factors of Obstructive Sleep Apnea Syndrome in Hypertensive Patients with Obesity in the Practice of Physician-Internist - Radchenko O.; Bek N.; Zvorska I.; Mykulynets R. (Львівський клінічний вісник)
Introduction. Obstructive sleep apnea (OSA) – a condition accompanied repeated, stop of breathing due to complete (apnea) or partial (hypopnea) narrowing of the airways during sleep at throat and termination of pulmonary ventilation with preserved respiratory effort which appears snoring, reduced partial pressure Blood oxygen, fragmentation of sleep with frequent short-term awakening and daytime sleepiness. Awakening becomes a protective mechanism that activates muscles-dilators of the upper respiratory tract and prevents asphyxiation. Aim. To review the literature on sleep disorders in medical practice of internists, to identify the risk factors of OSA in patients with essential hypertension (EH) and obesity (OB). Materials and methods. A review of literary sources on clinical signs and diagnoses of OSA syndrome was made. We examined 41 patients with EH of the 2nd stage, 1-3rd degree and 1st degree of gynecology. The CG included 27 people (15 men and 12 women) aged 50.2±2.2 years with a body mass index (BMI) 34.0±1.0 kg/m2, with complaints of snoring and sleep disorders. The CG included 14 people (7 men and 7 women) at the age of 47.1 ± 2.9 years, with BMI 31.5±1.1 kg/m2. All the patients were routinely screened according to the Ministry of Health of Ukraine N 384 dated May 24, 2012, and were interviewed by the American Apnea Sleep Association questionnaire. Results. The main symptoms that help to suspect OSA are neurocognitive: pronounced daytime sleepiness, annoyance, weakening of memory and attention, suppression of emotions, apathy, intellectual degradation. The increase of the severity of the syndrome leads to disorders of the cardiovascular system, in particular, increased blood pressure, occurrence of atrial and ventricular arrhythmias. In the main group of surveyed patients, the average score of the questionnaire was 12.6 points. All men and 91.7% of women showed a high probability of sleep apnea (> 10 points). In CG the average score was 7.4 points (p<0.05), and a high probability of sleep apnea was detected only in 3 persons. It is important that EH with OB and snoring were associated with the presence of nodes in the thyroid gland. Moreover, the higher score of the questionnaire means the larger sonographic size of the node. In addition, in the patients from the experimental group were significantly higher waist circumference (108 (102; 110) cm vs. 99 (89; 108) cm, p<0.05), systolic and pulse arterial pressure (160 (160 ; 180) vs 150 (140; 160) mm Hg, p <0.05) and (70 (60; 90) vs 60 (50; 60) mm Hg, p <0.05) than in the persons of the CG, which is evidence of a higher cardiovascular risk in such patients. Conclusions. In patients with EH, stage II, 1-3th degree with OB of 1st degree that were snoring at night revealed very high likelihood of OSA. Snoring is associated with a higher waist circumference, higher levels of systolic and pulsed arterial pressure, and frequent detection of nodular goiter, requiring special attention for internists, cardiologists and endocrinologists.